"A GEOECOLOGIA DA PAISAGEM COMO BASE PARA A ADEQUAÇÃO DE ZONAS DE AMORTECIMENTO EM MONUMENTOS NATURAIS E PARQUES NO ESTADO DE MATO GROSSO DO SUL" - Rafael Martins Brito (2023)
In the midst of intense changes in land use and land cover and impacts caused by human activities, Conservation Units (CU) have consolidated themselves worldwide as one of the main strategies for maintaining biodiversity and protecting aspects related to the landscape. This dynamic has been evidenced in recent decades in the Cerrado biome, especially in the state of Mato Grosso do Sul. Natural monuments, a category linked to the uniqueness of the landscape, are fundamental in the protection of environmental, cultural and social values. In this context, the main objective was to propose, based on the study of landscape units, an alternative for delimiting and adapting the Buffer Zones (ZA) of the CU called Serra do Bom Jardim Natural Monument (MNSBJ), Serra do Bom Sucesso Natural Monument (MNSBS) and Parque Natural Templo dos Pilares (PNMTP), located in the upper Taquari watershed, in Mato Grosso and Mato Grosso do Sul. The research was structured in seven articulated and complementary stages, based on a main axis rooted in methodological procedures based on the Geoecology of Landscapes to obtain a synthesis map of landscape units. Ordered and hierarchical physicalgeographical variables were used in a process of crossing and overlapping information in GIS. Five first-level landscape units (localities), 14 second-level units (Comarcas) and 28 third-level units (Subcomarcas) were identified. It derived from the classified landscape units indicators of naturalness, uniqueness and diversity, in support of the proposed delimitation of the ZA, with the support of already consolidated criteria for this purpose. The results obtained indicated that the delimitation based on these indicators is satisfactory as it comprises areas with the potential to coherently articulate the attributes that value Natural Monuments, in the same way that it seeks to satisfy the lack and/or lack of coverage with headwaters of the Taquari river, it incorporates areas of remarkable scenic beauty, integrates areas susceptible to negative impacts and collaborates for the connectivity of the Emas-Taquari-Pantanal corridor.incorporates areas of remarkable scenic beauty, integrates areas susceptible to negative impacts and collaborates for the connectivity of the Emas-Taquari-Pantanal corridor.